2021
DOI: 10.1186/s12891-021-04288-4
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Rotator Cuff Tears with platelet rich plasma: a prospective study with 2 year follow‐up

Abstract: Background Surgical treatment of full-thickness rotator cuff (RC) tears is associated with generally good results. There is no consensus regarding treatment of partial thickness tears that fail conservative treatment. The purpose of this study was to look at the efficacy and confirm the safety of dual injection PRP into the shoulder of patients with rotator cuff pathology who have failed conservative treatment with followup to two years. Methods Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Due to the risk of surgery, reduced strength of RC tendons, and a significant risk of injury recurrence, conservative options are the first choice, especially in older adults [11,12]. These conservative procedures comprise physical therapy and pharmacotherapy with steroid injections for anti-inflammatory effects, platelet-rich plasma (PRP), collagen injections, and autologous conditioned serum (ACS) for regenerative effects, as well as rehabilitation management [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the risk of surgery, reduced strength of RC tendons, and a significant risk of injury recurrence, conservative options are the first choice, especially in older adults [11,12]. These conservative procedures comprise physical therapy and pharmacotherapy with steroid injections for anti-inflammatory effects, platelet-rich plasma (PRP), collagen injections, and autologous conditioned serum (ACS) for regenerative effects, as well as rehabilitation management [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the Level of Evidence, 5 studies were level I RCTs 30,31,34,37,38 ; 5 level III PCC studies 7,8,32,33,42 ; and 1 level IV prospective case-series study 36 …”
Section: Resultsmentioning
confidence: 99%
“…Another meta-analysis by Wang et al assessed the safety of PRP in arthroscopic full-thickness rotator cuff repair. They found that PRP was safe and effectively improved the short-term outcomes following arthroscopic repair of full-thickness rotator cuff tears (72). Another study by Prodromos et al looking at the efficacy and safety of L-PRP in rotator cuff tears found that dual injections of L-PRP into the shoulder was safe and effective in patients that failed conservative treatment (73).…”
Section: Safety Of Prp Application In the Shouldermentioning
confidence: 99%
“…They found that PRP was safe and effectively improved the short-term outcomes following arthroscopic repair of full-thickness rotator cuff tears ( 72 ). Another study by Prodromos et al looking at the efficacy and safety of L-PRP in rotator cuff tears found that dual injections of L-PRP into the shoulder was safe and effective in patients that failed conservative treatment ( 73 ). However, Schwitzguebel et al , in their RCT, found that P-PRP was associated with higher incidence of adverse events such as pain, frozen shoulder and extension of the lesion compared to saline at more than 1 year of follow-up ( 26 ).…”
Section: Safety Of Prp Application In the Shouldermentioning
confidence: 99%